Succession of a british national resident in Spain: renvoi, again, as a decisive element between freedom to make a will and the legitimate successory rights, typical of the Spanish Common Civil Law - García Gutiérrez, Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In this cassation appeal, resolved by the Spanish Supreme Court, the admissibility of the renvoi in the succession of a British national that affects the ownership of a property located in Spain is considered. The Court emphasizes its doctrine limiting the role of renvoi when it leads to the fragmentation of the succession. In line with this idea, it analyzes the concept of domicile in English Law and the incidence of the foundation of a Trust according to the Law of Malta in the succession of the deceased.
Keywords: law applicable to succession; Freedom to make a will; Law applicable to Spanish “legítima sucesoria”; Renvoi; Trust founded according to a Foreign Law on goods located abroad